Testing the Hypothesis of Biofilm as a Source for Soft Tissue and Cell-Like Structures Preserved in Dinosaur Bone - Schweitzer, Mary Higby; Moyer, Alison E.; Zheng, Wenxia (PLOS ONE, 2016)
Recovery of still-soft tissue structures, including blood vessels and osteocytes, from dinosaur bone after demineralization was reported in 2005 and in subsequent publications. Despite multiple lines of evidence supporting an endogenous source, it was proposed that these structures arose from contamination from biofilm-forming organisms. To test the hypothesis that soft tissue structures result from microbial invasion of the fossil bone, we used two different biofilm-forming microorganisms to inoculate modern bone fragments from which organic components had been removed. We show fundamental morphological, chemical and textural differences between the resultant biofilm structures and those derived from dinosaur bone. The data do not support the hypothesis that biofilm-forming microorganisms are the source of these structures.